A study on treatment outcomes in MDR-TB patients on long term regimen in West Godavari district - Vasavi, Gedela; Neerugatti, Banerji; Kumar, Chiranjeevi Uday; Jagannadha Rao, Hari (International Journal of Basic & Clinical Pharmacology, 2021)
Background: MDR-TB is defined as a TB patient whose biological specimen is resistant to isoniazid and rifampicin with or without resistant to other first line drugs, based on results from quality assured laboratory. The main aim of this study was to study the treatment outcomes of longer regimen for MDR-TB patients. Methods: This is a retrospective observational cohort study. After obtaining ethical committee approval from Institutional ethics committee, data was collected from district TB centre from 2011-2016. Outcomes of a regimen is measured in terms of cured, treatment completed, number of defaulters, treatment failure, number of patients shifted to XDR-TB regimen, number of patients died for patients on longer regimen of MDR-TB. The collected data was entered in Microsoft excel 2007 and analysed using SPSS version 20 software. Results: Out of 211 patients, 167 were males and 44 were females. The total numbers of patients registered from rural areas were 123 and from urban areas were 88. The association between geographical distribution and treatment outcome was measured using Chi-square test and X2=12.1026, p=0.0005 which was significant. Out of 211 patients registered, 87 (41.2%) were cured of disease, 55 (26%) died, 2 (0.9%) patients shifted to XDR. 18 (8.5%) patients were defined as defaulters and 2 (0.9%) patients were defined as treatment failures. Conclusions: Our study findings have indicated that treatment outcomes in drug resistant TB may be influenced by rural and urban distribution.